Synthesis, Characterization and Antimicrobial Activity of N-(N,NDiethylaminobenzyl) thiosemicarbazone and Its Transition Metal Complexes - Mohamed Kasim, A.N.; Srinivasan, R. (Asian Journal of Chemistry, 2010)
The new Mannich base N-(N,N-diethylaminobenzyl)thiosemicarbazone is synthesized by condensing N,N-diethylamine, benzaldehyde and thiosemicarbazide and characterized by elemental analysis, FT IR and PMR spectral data. Solid complexes of N-(N,N-diethylaminobenzyl)- thiosemicarbazone with bivalent Mn, Co, Ni, Cu and Cd metal salts have been synthesized and characterized by elemental analysis, conductance, UV, IR and PMR spectral and DTA studies. The ligand acts as the bidentate coordinating through the N of diethylamine and S of thiosemicarbazide moieties. The ligand and the complexes have also been screened for in vitro disc diffusion studies for antimicrobial activities.